The contribution of load magnitude and number of load cycles to cumulative low-back load estimations: A study based on in-vitro compression data - Coenen, Pieter; Kingma, I.; Boot, C.; Bongers, P.; Van Dieën, J. (2012)
Background: Cumulative low-back load is suggested to be associated with low back pain, possibly due to (micro-)fractures of spinal segments. Based on available in vitro data it can be assumed that, in order to predict spine segment failure from cumulative compressive loading, load magnitude should be weighted with an exponent higher than one, whereas the number of cycles should be weighted with an exponent lower than 1. The aim of the present study was to assess both exponents based on available in-vitro data. Methods: Data on loading to fatigue fracture of spinal segments under cyclic compression in-vitro were used and converted to survival probability for 5 load levels and 5 levels of number of cycles. Three optimization procedures were used to estimate the exponent of load magnitude and load cycles separately, and load magnitude and load cycles combined. Goodness of fit was assessed by comparing the Akaike's Information Criterion (AIC) between models. Findings: The best fit, based on AIC and average error per data point was obtained with weighting of load magnitude and number of load cycles with exponents of approximately 2.0 and 0.2, respectively. Interpretation: The results show that a combination of load magnitude and number of load cycles weighted with exponents of approximately 2 and 0.2 respectively provides a suitable measure of cumulative spinal compression loading. This finding may be of relevance for assessing cumulative low-back loads in studies on the etiology of low-back pain. © 2012 Elsevier Ltd.